The 23rd 'Artists Today' Exhibition : Phases - Material, Tableau and Apocalypse. - Artists Today Exhibition, Yokohama, 1987 (Yokohama : Shimin Gyarari, 1987)
Toyohira, Yoshio ; Kuniyasu, Takamasa ; Nose, Kojiro ; Odanaka, Yasuhiro ; Sakaguchi, Susumu ; Shiba, Akifumi ; Nakamura, Kazumi ; Yajima, Mieko ; Nakagawa, Masaaki ; Tsuji, Kei ; Sugano, Yumiko
The 23rd 'Artists Today' Exhibition : Phases - Material, Tableau and Apocalypse, Yokohama, 19.11 - 03.12.1987
boek